Contractors role in creating safe urban areas A case study of Skanska’s safety efforts in Kvibergs Ängar - COTRA, NEVENA; KAREM SHWAN, DIANA (My University, 2020)
The City of Gothenburg is facing big challenges in terms of urban development as it is growing rapidly. This creates pressure on contractors to build more socially sustainable in order to help produce a shift toward a more inclusive, connected and less fragmented city. A district which has been undergoing extensive urban development in recent years is Kviberg. Kviberg has for a long time been characterized as an unattractive district due to its reputation of being unsafe. Skanska is one of several actors who have been involved in trying to develop Kviberg into a more attractive and safe residential district with their pilot project called Kvibergs Ängar where a particular focus has been placed on increasing neighbourhood safety. The aim of this master thesis is to investigate how contractors can contribute to social sustainability in urban development by creating safe urban areas. By studying Skanska’s safety eﬀorts in Kvibergs Ängar, an analysis has been made on what the opportunities and challenges are for contractors when trying to create safer urban areas. An abductive research methodology was applied, starting with a case study of Skanska’s safety eﬀorts in Kvibergs Ängar. This was followed by a literature review, observations, interviews and a questionnaire to form an understanding of how safety is perceived in Kviberg. In conclusion, this study argues that “sense of community” and “feeling of safety in the built environment” are two fundamental elements of social sustainability. In the context of Kviberg, results show that place qualities in the built environment are importantforhowpeopleperceiveandusespaceandthattheycaneitherincreaseor decrease the feeling of safety. By creating urban areas with certain place qualities, contractorscancontributetosocialsustainability. InthecontextofKvibergsÄngar, contractors could only do so much, as the responsibility to create inclusive and safe urban areas does not lie entirely on contractors. Further, a prerequisite for creating safe urban areas is local collaboration, such as BID-inspired collaborations. By collaborating locally, diﬀerent actors can mutually decide what they want to achieve and how to achieve it, in a particular area. The ﬁndings also show that detailed development plans can be a restricting factor for contractors as they do not allow ﬂexibilitytomeetchangingneeds. Lastly,theﬁndingsshowthatprojectdevelopers, in general, weigh diﬀerent interest against each other. As a consequence, safety is sometimes overshadowed by other interests.
Keywords: Social sustainability; Safety; Kvibergs Ängar; Skanska; Business Improvement District; BID